Successful use of Netakimab in the treatment of psoriasis accompanied by the psoriatic onychodystrophy - N. N. Potekaev; O. V. Zhukova; S. I. Artemyeva (Медицинский совет, 2020)
Psoriasis is a chronic immune-mediated disease that is accompanied by a significant number of comorbid pathologies. Damage to the nail plates (psoriatic onychodystrophy) is widespread among patients with psoriasis and is associated with significant functional as well as psychosocial impairments. Despite the fact that nails constitute a small percentage of the surface of the human body, the damage to this particular area can lead to a deterioration in the quality of life and irreversible disability. In addition, studies have shown that nail psoriasis is indicative of a more severe course of the disease and it can also be associated with psoriatic arthritis or it can be a predictor of its development. Current treatment options for psoriasis accompanied by the nail plates damage include many topical and systemic methods, however, patients often report dissatisfaction with the results of treatment due to low efficacy or many side effects. Achieving higher efficiency is possible with the use of biologic therapy. Currently, a wide range of biologics have been developed that modulate key elements in the immunopathogenesis of psoriasis.The pathogenesis of psoriasis is a multifactorial process, however, it is the IL23 / Th17 signaling pathway that is key in this process. Interleukin-17A is the principal effector of this pathway and overexpression of IL-17A leads to epidermal hyperplasia and an excessive inflammatory response seen in psoriasis. Therefore, interleukin-17A is a promising therapeutic target.Considering the critical pathogenetic role as well as the high efficacy and safety of IL-17A inhibitors, the study of their effect on the psoriatic onychodystrophy manifestations is of great clinical importance.Netakimab is the first Russian original IL-17 inhibitor which is a promising modern agent for the treatment of moderate-to-severe plaque psoriasis. The obtained real clinical data indicate the high efficacy and safety of the use of Netakimab in patients with both plaque psoriasis and «severe» psoriasis in difficult to treat localizations, such as damage of the nail plate.